2023
DOI: 10.46557/001c.38781
|View full text |Cite
|
Sign up to set email alerts
|

Climate Policy Uncertainty and Crude Oil Market Volatility

Abstract: In this study, we pursue two main innovations. First, we evaluate the predictive value of climate policy uncertainty (CPU) for oil market volatility. Second, we demonstrate how an investor can exploit the information contents of CPU to gain higher returns. We find that increased values of CPU heighten crude oil market risk, while higher forecast gains are achieved in a model that accommodates CPU. We further show that observing CPU offers higher portfolio returns than ignoring it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…More importantly, we find the shock persistence of the combined ARCH and GARCH effects close to unity in the model that includes the role of climate risk compared to the model without the role of climate risk, thus validating our hypothesis that climate risk amplifies the persistence of volatility in the oil markets. Our findings in this regard find support in Salisu et al (2022), where climate risk was previously established as capable of fueling higher uncertainties in the global crude oil market. However, and quite innovative in the context of this study, is the fact that the extent to which climate risk amplifies volatility in the oil markets tends to vary for different indicators of oil market volatility.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…More importantly, we find the shock persistence of the combined ARCH and GARCH effects close to unity in the model that includes the role of climate risk compared to the model without the role of climate risk, thus validating our hypothesis that climate risk amplifies the persistence of volatility in the oil markets. Our findings in this regard find support in Salisu et al (2022), where climate risk was previously established as capable of fueling higher uncertainties in the global crude oil market. However, and quite innovative in the context of this study, is the fact that the extent to which climate risk amplifies volatility in the oil markets tends to vary for different indicators of oil market volatility.…”
Section: Resultssupporting
confidence: 77%
“…One of the novelties of this study is the use of alternative measures of oil market volatility. On the one hand, we follow the common practice in the literature to measure oil market volatility in terms of the returns of WTI 2 crude oil prices in a GARCH framework (see Salisu et al, 2022). We further complement this approach to modelling volatility in the oil market with the CBOE crude oil ETF volatility index (OVX).…”
Section: A Data and Preliminary Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Investors choose this asset class as their preferred investment or trading instrument to generate higher profits. However, policy changes aimed at achieving zero‐net emissions goals and shocks in the energy market may lead to significantly higher volatility and risks for energy‐commodity investments (Hoque, Soo‐Wah, & Billah, 2023; Liu et al, 2022; Ren et al, 2023; Salisu et al, 2022; Wang et al, 2023). Previous empirical studies of hedging and safe‐haven instruments for energy commodities have identified several asset classes, such as green bonds (Mokni et al, 2022), carbon assets (Lee & Yoon, 2020; Uddin et al, 2018), precious metals (Hernandez et al, 2019; Salisu et al, 2021), and Cryptocurrency (Bouri, Molnár, et al, 2017; Lee & Yoon, 2020; Uddin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The literature has equally provided enough evidence to suggest that temperature patterns can impact the economy via different channels. In particular, temperature changes have a great influence on per capita income (see [4]), labor productivity and sales volume [5][6][7], manufacturing export [8], and performance of commercial real estate investment [9]. Other related studies provide links between climate change and stock returns.…”
Section: Introductionmentioning
confidence: 99%